2015
DOI: 10.1111/mmi.12985
|View full text |Cite
|
Sign up to set email alerts
|

The endosomal sorting complex required for transport machinery influences haem uptake and capsule elaboration in Cryptococcus neoformans

Abstract: Summary Iron availability is a key determinant of virulence in the pathogenic fungus Cryptococcus neoformans. Previous work revealed that the ESCRT (endosomal sorting complex required for transport) protein Vps23 functions in iron acquisition, capsule formation and virulence. Here, we further characterized the ESCRT machinery to demonstrate that defects in the ESCRT-II and III complexes caused reduced capsule attachment, impaired growth on haem and resistance to non-iron metalloprotoporphyrins. The ESCRT mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 76 publications
(183 reference statements)
4
85
0
Order By: Relevance
“…88 An additional study showed that other ESCRT proteins, specifically Vps22 (ESCRT-II) and Snf7/ Vps20 (ESCRT-III), also contribute to heme use in C. neoformans . 89 Similar to C. albicans , a putative hemophore, Cig1, has also been described in C. neoformans that is involved in heme binding, uptake and virulence. 90 The Cig1 protein does not contain a CFEM domain and therefore must interact with heme via a different mechanism than the C. albicans proteins.…”
Section: Heme and Hemoglobin Are Important Iron Sources For Pathogmentioning
confidence: 99%
“…88 An additional study showed that other ESCRT proteins, specifically Vps22 (ESCRT-II) and Snf7/ Vps20 (ESCRT-III), also contribute to heme use in C. neoformans . 89 Similar to C. albicans , a putative hemophore, Cig1, has also been described in C. neoformans that is involved in heme binding, uptake and virulence. 90 The Cig1 protein does not contain a CFEM domain and therefore must interact with heme via a different mechanism than the C. albicans proteins.…”
Section: Heme and Hemoglobin Are Important Iron Sources For Pathogmentioning
confidence: 99%
“…Reduced transcript levels of these genes were well correlated with the growth deficiency of the rim101 Δ mutant in low-iron media (O’Meara et al ., 2010). Furthermore, a series of recent studies showed that both the cig1 Δ mutant and the rim101 Δ mutant were defective in heme uptake and that Rim101 plays a role in heme utilization via the ESCRT machinery, although evidence for a Rim101-independent heme uptake pathway was also obtained (Cadieux et al ., 2013; Hu et al ., 2015). …”
Section: Downstream Targets Of the Camp/pka Pathway: Transcription Famentioning
confidence: 99%
“…A screen for functions needed for growth on heme revealed that proteins of the endosomal sorting complex required for transport (ESCRT) participate in iron acquisition, as well as in capsule formation and virulence (Hu et al ., 2013, 2015). Interestingly, ESCRT functions are also required in fungi for the activation of Rim101 (Selvig and Alspaugh, 2011; Ost et al ., 2015).…”
Section: Downstream Targets Of the Camp/pka Pathway: Transcription Famentioning
confidence: 99%
See 2 more Smart Citations